2006
DOI: 10.1111/j.1467-9620.2006.00699.x
|View full text |Cite
|
Sign up to set email alerts
|

The Context of Minority Disproportionality: Practitioner Perspectives on Special Education Referral

Abstract: Although there is extensive documentation of minority overrepresentation in special education, knowledge of the factors that create the context within which disproportionality occurs is limited. To gain an understanding of the local processes that may contribute to special education disproportionality, we interviewed 66 educators about their perspectives on urban education, special education, available and needed resources, and the specific topics of diversity and disproportionality. A number of clear themes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 25 publications
2
53
0
Order By: Relevance
“…Furthermore, they found the WISC-III identified more African American children as mentally retarded compared to the CAS. Other research with similar findings (Ebersole & Kapp, 2007;Skiba, Simmons, Ritter, Kohler, Henderson, & Wu, 2006) indicated a direct link to the overrepresentation of African American children in programs for the mentally retarded and the strict cutoff of a 70 IQ.…”
Section: Racial Differences In Intelligencementioning
confidence: 63%
See 2 more Smart Citations
“…Furthermore, they found the WISC-III identified more African American children as mentally retarded compared to the CAS. Other research with similar findings (Ebersole & Kapp, 2007;Skiba, Simmons, Ritter, Kohler, Henderson, & Wu, 2006) indicated a direct link to the overrepresentation of African American children in programs for the mentally retarded and the strict cutoff of a 70 IQ.…”
Section: Racial Differences In Intelligencementioning
confidence: 63%
“…These questions are particularly important considering the overrepresentation of African Americans in special education across the country (Skiba et al, 2006). Research indicated a direct link to the overrepresentation of African American children in programs for the mentally retarded and the strict cutoff of a 70 IQ (Ebersole & Kapp, 2007).…”
Section: Implications Of An Iq Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ethnic bias in identification and assessment for SEN (Knotec, 2003) and disproportionate referral to special education provision of students from socioeconomically disadvantaged or minority ethnic groups have been viewed as problematic and a concern by researchers and policy makers. However teachers and professionals such as psychologists assessing the student may view special education as a positive goal (Harry & Klinger, 2006;Skiba, Simmons, Ritter, Kohler, Henderson, & Wu, 2006). These views may be a function of practitioners struggling with inadequate preparation, an inappropriate curriculum and pedagogy (Blanchett, 2006) as well as inadequate resources.…”
Section: Implications For the Conceptualisation Of Disproportionalitymentioning
confidence: 99%
“…(Skiba et al, 2006(Skiba et al, , p. 1426 Sullivan and Artiles (2011) explained that structural inequity theory applies when a systematic bias is demonstrated by a patterned and differential distribution of resources, life chances and costs/benefits among groups of the population that result in structural inequities. Structural or institutional racism is defined by Bonilla-Silva (1996) as having the following characteristics; it is covert, embedded in normal operations, avoids direct racial terminology and is invisible to most white persons.…”
Section: Structural Inequity Theorymentioning
confidence: 99%